Body Composition Changes and Associations in Infants and Mothers During the First Year: Insights from a Pilot Study of the Baby-bod Project - Manoja P. Herath; Kiran D. K. Ahuja; Jeffrey M. Beckett; Sisitha Jayasinghe; Nuala M. Byrne; Andrew P. Hills (Children)
Background: The period following childbirth is marked by dynamic changes in maternal physiology and the growth trajectory of the newborn. We aimed to elucidate the changes and associations in body composition of infants and their mothers during the first year postpartum. Methods: This pilot study assessed infant body composition using the PEA POD air displacement plethysmography (ADP) system (birth–6 months) and deuterium dilution (9–12 months). Maternal body composition was assessed using the BOD POD ADP system at 12 months postpartum. Mothers were grouped by prepregnancy body mass index (BMI) <25 kg/m2 (lean) or ≥25 kg/m2 (overweight/obese: OW/OB), and data were analysed using linear regression. Results: Twenty-nine infant–mother pairs were assessed. Infant percent fat mass (%FM) increased from birth to 6 months (9.3% vs. 24.2%; p < 0.001) and then gradually declined. At birth and 3 months, %FM was significantly higher in infants born to OW/OB mothers compared to their lean counterparts. A significant positive association (β = 0.3; p = 0.040) was observed between maternal %FM and infant %FM at 1 year post-delivery after controlling for the mother’s prepregnancy BMI. Conclusions: Infants born to OW/OB mothers have increased %FM at birth and 3 months, which may have consequences for their health throughout childhood and into adulthood. Moreover, maternal prepregnancy BMI is a significant predictor of maternal postpartum weight status and body composition and impacts the relationship between maternal and infant body composition at 12 months postpartum. While the findings of our pilot study underscore the importance of encouraging women of childbearing age to maintain a healthy BMI before conception, further research is needed to substantiate these results.